Performance-Based Executive Function Instruments Used by Occupational Therapists for Children: A Systematic Review of Measurement Properties - Ivan Neil B. Gomez; Sharleen Alyssa M. Palomo; Ana Melissa U. Vicuña; Jose Antonio D. Bustamante; Jillian Marie E. Eborde; Krishna A. Regala; Gwyn Marie M. Ruiz; Andrea Lorraine G. Sanchez (Hindawi-Wiley, 2021)
Introduction. The use of executive function (EF) instruments to assess children's functional performance is obscured with a lack of consensus on which is most suitable to use within the occupational therapy profession. This review identifies EF instruments used by occupational therapists (OTs) for children and evaluates their measurement properties. Methods. This systematic review was registered in PROSPERO (CRD42020172107). We reviewed occupational therapy-related studies published until March 2021, to identify performance-based EF instruments used among children by OTs. Two review authors independently screened, extracted, and evaluated the methodological rigor of the included studies. Adequacy of the measurement properties was determined using the COSMIN, and the Terwee criteria were used for synthesis of best evidence. Results. Five EF assessments were found across eight study articles: Behavioural Assessment of the Dysexecutive Syndrome for Children, Children's Cooking Task, Children's Kitchen Task Assessment, Do-Eat, and Preschool Executive Task Assessment. Adequacy of measurement properties and synthesis of best evidence varied, leading to a low GRADE rating on the certainty of evidence for the included instruments. Conclusions. There is limited evidence that supports the certainty of evidence on the measurement properties of the reviewed tools in helping OTs assess performance-based EF among children. Nevertheless, the authors conditionally suggest their use based on the critical need to measure children's EF. Further research is needed to establish the measurement properties of these measures across different childhood populations.